A mini-review on phytochemistry and pharmacological activities of Scrophularia striata - Pari Tamri (Shahrekord University of Medical Sciences, 2019)
Introduction: Scrophularia striata (Scrophulariaceae) is an important medicinal plant in Iran and in Iranian folk medicine it has been used for variety of disorders. The present article aims to provide a review at the studies done on phytochemistry and pharmacological effects of S. striata. Methods: This mini review is based on a literature study of scientific journals from electronic sources, such as Science Direct, PubMed, Google Scholar, Scopus and Web of Science. Results: The main chemical constituents which have been isolated and identified from Scrophularia striata are cinnamic acid, some flavonoids such as quercetin, isorhamnetin3-O-rutinoside and nepitrin and one glycoside (acteoside1) . This plant possesses antiinflammatory , antibacterial , antioxidant, anticancer, analgesic and neuroprotective effects. In addition it accelerates wound healing process Conclusion : Scrophularia striata has a potential for the treatment of several diseases and disorders, but there are only a few studies done to investigate the plant phytochemistry, thus f urther studies should be focused on isolation and identification of active compounds with pharmacological activities. Besides, the majority of pharmacological studies have been performed using aerial parts of plant , thus further studies are needed to investigate bioactivity of other parts of the plant.